Perlindungan Hukum bagi Penggadai Tanah Pertanian dihubungkan dengan Undang-Undang Nomor 56 Tahun 1960 Tentang Penetapan Luas Tanah Pertanian - Andri Susanto; Yuniar Rahmatiar; Muhamad Abas (LPPM Universitas Ekasakti Padang, 2023)
One of the contents of Law Number 56 of 1960 concerning Determination of Agricultural Land Areas regulates the implementation of land mortgages. In reality, many mortgages last for years or even decades, and some are even continued by the heirs of the pawn holder, because the mortgagee is unable to buy back his land. The formulation of the problem in this study. First, what is the legal protection for pawning agricultural land based on Law Number 56 of 1960 concerning Determination of Agricultural Land Areas. Second, how to resolve disputes arising from the implementation of agricultural land mortgages. The purpose of the research is of course to answer the formulation of the problem in this research. This research is a normative research using a normative juridical approach. As for the results of the first study, protection for pawnbrokers eliminates the obligation to pay off debts if it has reached 7 years. Second, settlement of disputes arising from the implementation of land pledges can be pursued through non-litigation and litigation both civil and criminal.